An Overview of Clinical Oncology and Impact on Oral Health - Harris, Jack A.; Ottaviani, Giulia; Treister, Nathaniel S.; Hanna, Glenn J. (Frontiers in Oral Health, 2022)
As the incidence of cancer continues to increase, so too will the use of various forms of cancer therapeutics and their associated oral and dental complications. Although many of the acute and chronic oral toxicities of cancer therapy are largely unavoidable, appropriate and timely management of these complications has the potential to alleviate morbidity and improve outcomes. Undoubtedly, the substantial short- and long-term impacts of cancer therapy on the health of the oral cavity requires increased awareness, prevention, and treatment by multidisciplinary healthcare teams consisting of medical oncologists, dentists, and other oral healthcare specialists. This mini review provides a brief purview of the current state of clinical oncology and its impact on oral health. The topics introduced here will be further investigated throughout the remainder of the “Oral Complications in Cancer Patients” mini-review series.